Fenologia, Produção e Pós-colheita de frutos de buriti (Mauritia flexuosa L.f) em três veredas do cerrado no estado de Goiás. - MARTINS, Maria Lúcia (2010)
This study aimed to characterize the phenology, production and post-harvest fruit of the buriti palm tree in the Savannah as well as factors impacting on production. The study was conducted in three palm swamp with three distinct forms of occupation of the borders. The buriti palm tree were characterized as height, diameter at breast height, number of inflorescences and leaves. The number of leaves was correlated with climatic data from July 2006 to September 2009. To characterize the production were collected from three clusters per area, and determined the average weight of fruit bunches and these extrapolated data for each area. In three clusters of each palm swamp included: length of the bunch, bunch weight, fruit weight, number of rachilles, and fruit number, length rachilles, total number of loci, number of loci with fruit, no fruit locule number , and the reason the number of loci with fruits / total number of loci. Characterization were carried out fifty fruits of each of the three clusters collected in each area. The characterization of fruits were evaluated: fruit weight, diameter longitudinal, transverse diameter, transverse diameter ratio / longitudinal diameter, the pulp mass, mass of bark, seed mass, and mass of endocarp. The pulp included: pH, total titratable acidity as citric acid, moisture and minerals. In a second phase were collected in five months, 250 fruits per area, per collection, where in addition to the analysis in the fruit pulp and cited, were analyzed for crude fiber, protein, lipid and fatty acid profile in the pulp the fruits of the first and last collection. Finally, was evaluate different treatments of artificial ripening of buriti. To check on what treatment get more uniform ripening counted the number of mature fruits, hard and dirty. The pulp was found: pH, total acidity and citric acid, moisture, minerals and starch. The results of this study support the conclusion: In relation to phenology, the average number of leaves of buriti palm tree do not differ between plants and sex, however, have differ for maximum temperature. The palm swamp have average income calculated in pulp yield 651.54 kg ha-1. Fruits buriti have high nutritional content and is suitable for fresh consumption and processing purposes. Fruits buriti present average mass of 54.19 g of which 17.79% is pulp, seed 34.69%, 20.88% bark and 26.64% endocarp. The mineral elements examined during the five seasons had different values. The pulps of buriti show high content of fiber, reduced levels of lipids, being the predominant fatty acid, palmitic. The storage for seven days followed by immersion of fruits in water at 55 °C for thirty minutes is the treatment that has a higher yield in the process of maturation (95.5%).